Factors Associated With Clinical and Radiographic Severity in People With Osteoarthritis: A Cross-Sectional Population-Based Study - Costa, Daniela; Cruz, Eduardo B.; Silva, Catarina; Canhão, Helena; Branco, Jaime; Nunes, Carla; Rodrigues, Ana M. (Frontiers in Medicine, 2021)
Background: Hip/knee osteoarthritis (HKOA) is a leading cause of disability and imposes a major socioeconomic burden. The aim of this study is to estimate the prevalence of HKOA in Portugal, characterized the clinical severity of HKOA in the population, and identified sociodemographic, lifestyle, and clinical factors associated with higher clinical and radiographic severity. Methods: Participants with a diagnosis of HKOA from the EpiReumaPt study (2011-2013) were included (n=1,087). HKOA diagnosis was made through a structured evaluation by rheumatologists according to American College of Rheumatology criteria. Clinical severity was classified based on Hip Disability and Osteoarthritis Outcome Scale (HOOS) and Knee Injury and Osteoarthritis Outcome Scale (KOOS) score tertiles. Radiographic severity was classified based on the Kellgren-Lawrence grades as mild, moderate, or severe. Sociodemographic lifestyle and clinical variables, including the presence of anxiety and depression symptoms, were analysed. Factors associated with higher clinical and radiographic severity were identified using ordinal logistic regression models. Results: HKOA was present in 14.1% of the Portuguese population (12.4% with knee OA and 2.9% with hip OA). Clinical severity was similar between people with hip (HOOS=55.79±20.88) and knee (KOOS=55.33±20.641) OA. People in the high HOOS/KOOS tertile tended to be older (64.39±0.70 years), female (75.2%), overweight (39.0%) or obese (45.9%) and had multimorbidity (86.1%). Factors significantly associated with higher clinical severity tertile were age (55-64 years: odds ratio (OR)= 3.18; 65-74 years: OR=3.25; ≥75 years: OR=4.24), female sex (OR=1.60); multimorbidity (OR=1.75), being overweight (OR=2.01) or obese (OR=2.82), and having anxiety symptoms (OR=1.83). Years of education was inversely associated with higher clinical severity. Factors significantly associated with higher radiographic severity were age (65-74 years: OR=3.59; ≥75 years: OR=3.05) and being in the high HOOS/KOOS tertile (OR=4.91). Being a female and live in Lisbon or in the Centre region were inversely associated with the higher radiographic severity. Conclusion: Age, educational level, and obesity are independently associated with HKOA clinical severity. These findings reinforce the need for effective prevention and management strategies to avoid HKOA progression, namely programs for weight loss and control of chronic non-communicable diseases.